2015
DOI: 10.1001/jamapediatrics.2014.1889
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Anomalies and In Utero Antiretroviral Exposure in Human Immunodeficiency Virus–Exposed Uninfected Infants

Abstract: Importance Most studies examining the association of prenatal antiretroviral exposures with congenital anomalies (CAs) in children born to HIV-infected women have been reassuring, but some suggest increased risk with specific antiretrovirals. Objectives To evaluate associations of in utero antiretroviral exposures with CAs in HIV-exposed uninfected children. Design prospective cohort study, the Pediatric HIV/AIDS Cohort Study (PHACS) Surveillance Monitoring of ART Toxicities (SMARTT) study. Setting 22 US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 32 publications
(47 reference statements)
1
49
0
Order By: Relevance
“…Several studies have shown relationships between ATV and delayed language development 2830 and social– emotional development. 30 First-trimester ATV use has also been linked to an increased risk of skin and musculoskeletal malformations, 16 and in utero TDF exposure may be linked to reduced bone mineral content in infants. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown relationships between ATV and delayed language development 2830 and social– emotional development. 30 First-trimester ATV use has also been linked to an increased risk of skin and musculoskeletal malformations, 16 and in utero TDF exposure may be linked to reduced bone mineral content in infants. 14 …”
Section: Discussionmentioning
confidence: 99%
“…21,35,36 A comprehensive safety assessment must consider a wide range of possible adverse outcomes. However, we evaluated multiple domains of interest which could reflect mitochondrial dysfunction, epigenetic effects, or other mechanisms of toxicity related to intrauterine exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite earlier reports in humans revealing neural tube defects in infants exposed to efavirenz (EFV) early in gestation [99,109], a more recent meta-analysis of 2026 infants countered these results and found no risk (RR=0.78, 95% CI: 0.56–1.08) [93]. In addition, the French EPF [80] and a recent US study [101] found overall low rates of congenital anomalies associated with EFV.…”
Section: Discussionmentioning
confidence: 98%